The South Africa World Cup: No One Can Take Away the Party (Observatorio Económico, 2010)
Hosting a soccer World Cup is an event that stirs across-the-board joy in the society entrusted with it. Months later, however, when the bill arrives, not everyone is quite so happy.  That is why minimum wage increases in countries with high informality do not help improve income distribution. Major sporting events such as the World Cup and the Olympic Games are often presented as great opportunities to boost the host country's economy. Continue reading...
Keywords: South Africa World Cup; 2010 World Cup; GDP